Peran kebijakan fiskal syariah dalam mengembangkan ekonomi berbasis syariah: Pendekatan bibliometrik dan systematic literature review - Romadhona, Azhara (Maliki Interdisciplinary Journal, 2025)
This article explores the role of sharia fiscal policy in the development of a Sharia-based economy through a bibliometric and systematic literature review approach. Sharia fiscal policy integrates spiritual and moral values and focuses on wealth redistribution and social justice through instruments such as zakat, infaq and waqf. These instruments aim to reduce economic disparities and promote social justice. The study highlights the important role of fiscal policy in the Islamic economy, particularly in addressing crises through ethical financing alternatives. By using zakat, infaq and waqf, Shariah fiscal policy offers sustainable solutions without relying on interest-based debt. The paper also discusses the relevance of these policies in Indonesia, where the APBN's fiscal management reflects Sharia principles. Despite challenges in optimising public participation and asset management, the potential of Sharia-based fiscal instruments to promote inclusive economic growth and long-term social welfare remains high. This study contributes to the understanding of the role of fiscal policy in the Sharia economy and provides strategic recommendations for future development.